2014
DOI: 10.1039/c4cp00233d
|View full text |Cite
|
Sign up to set email alerts
|

A salt-bridge structure in solution revealed by 2D-IR spectroscopy

Abstract: We determine the spatial structure of a guanidinium:acetate salt bridge in solution from cross peaks in its 2D-IR spectrum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The salt-bridge structure is also investigated in this spectroscopic region. 37 To our best knowledge, the 2000-2800 frequency region has not been systematically used for identification of salt bridges and ionic interactions in peptides and proteins, e.g., see Refs. 103 and 104.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salt-bridge structure is also investigated in this spectroscopic region. 37 To our best knowledge, the 2000-2800 frequency region has not been systematically used for identification of salt bridges and ionic interactions in peptides and proteins, e.g., see Refs. 103 and 104.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic geometric analysis of the Brookhaven Protein Data Bank, the stereochemistry of the side-chain H-bonds of proteins was pointed out to be characterized by at least three factors: (a) the electronic configuration of the H-bond acceptor atoms, (b) the steric accessibility of the H-bond donor atoms, and (c) the conformation of amino acid side-chains. 27 There have also been a number of theoretical studies aimed at quantifying the strength of interaction of small ions, 9,15,26,[28][29][30][31][32][33][34][35][36][37] mimicking the salt bridges between the CO − 2 side group of glutamate or asparate and the guanidinium side group of the arginine. In particular, the interaction energy in the Arg-Glu salt bridge varies from 35 [45][46][47][48][49] The IR spectrum was evaluated in some papers; 45,49 however, the 2000-2800 frequency region was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…2D IR spectroscopy has been similarly applied to characterize the ligand exchange and solvation dynamics of a wide variety of ion pairs. 28, 39, 40 …”
Section: Applications Of 2d Ir Spectroscopymentioning
confidence: 99%
“…30 We found that two degenerate CN 3 D In the calculated spectra, the splitting between the MeGdm + and Ac − bands is larger for the side-on geometry, which indicates that the coupling strength is larger in this configuration than in the end-on geometry. For both geometries, a value for the coupling between the vibrational modes of MeGdm + and Ac − is difficult to estimate directly from the changes in the IR frequencies upon salt-bridge formation.…”
Section: A Isolated Salt Bridgementioning
confidence: 86%
“…30 In the ab initio calculation, the monodentate geometry of Figure 1(c) was not a global energy minimum (∆E > 9 kcal/mol), and therefore it is probably not significantly populated. However, it is worth noting that in this geometry, the high-frequency MeGdm Table S1 in the supplementary material 33 for the atom participation in the normal modes for all geometries).…”
Section: A Isolated Salt Bridgementioning
confidence: 99%